Immunotherapy in recurrent and or metastatic squamous cell carcinoma of the head and neck. Issue 3 (May 2019) - Saada-Bouzid, Esma; Peyrade, Frederic; Guigay, Joël
Abstract : Purpose of review: Checkpoint inhibitors (CPI) are revolutionizing the treatment of advanced cancers including recurrent and or metastatic squamous cell carcinoma of the head and neck (RM-SCCHN). Recent findings: In this review, we will summarize the results of prospective trials evaluating CPI and particularly antiprogrammed death 1 (PD-1)/antiprogrammed death-ligand 1 (PD-L1) in RM-SCCHN. Summary: Nivolumab and Pembrolizumab, two anti-PD-1 CPI, were associated with longer overall survival than standard chemotherapy in pretreated RM-SCCHN in two randomized phase 3 trials (respectively CHECKMATE-141 and KEYNOTE-040). Both are now approved in this setting. In the KEYNOTE-048 trial, the pembrolizumab was also associated with a longer survival when compared with the EXTREME regimen in first-line RM-SCCHN patients whose tumors overexpressed PD-L1 (combined positive score ≥20%). This trial also showed a superiority of platinum-based chemotherapy and pembrolizumab vs. EXTREME regimen in unselected first-line RM-SCCHN. Pembrolizumab will probably be the next standard of care for first-line RM-SCCHN with high expression of PD-L1. Further evaluation of CPI combined with other antitumoral agents is ongoing in advanced and locally advanced SCCHN.